Ação moduladora da própolis de Bijuí na atividade funcional de fagócitos mononucleares do sangue humano - Borges, Mauro Afonso da Silva (2017)
Propolis is a resinous product produced by bees and contains compounds made from substances collected in different regions of plants. Its chemical composition is related to the flora of each region, harvesting season of the material and the species of the bee. The modulating action of propolis obtained from bees of the genus Scaptotrigona is little known. However, studies with propolis obtained from different species of bees show that this compound has anti-inflammatory, antitumor, antioxidant and immunomodulatory activity. The activity of propolis can occur through the activation of peripheral blood mononuclear (MN) phagocytes, inducing the production of proinflammatory cytokines, as well as the generation of reactive oxygen species (ROS) balanced by the dosage of the enzyme superoxide desmutase (Cu- Zn SOD). These actions may promote increased phagocytic and microbicidal activity. The aim of this work was to evaluate the in vitro modulatory action of Scaptotrigona polysticta propolis in the functional activity of MN phagocytes in the peripheral blood. For this purpose, human peripheral blood samples were collected to obtain the MN phagocytes, which were divided into four groups: A-cell; B - cell + fungus; C - cell + propolis: D - cell + fungus + propolis. Cell viability, superoxide anion release (O2 •- ), Cu-Zn SOD enzyme production, phagocytosis and microbicidal activity were evaluated. The results showed that propolis did not interfere in cellular viability, being able to modulate MN phagocytes in the production of O2 •- and Cu-Zn SOD enzyme. In addition, it induced an increase in phagocytosis activity without modifying the microbicidal action of these cells. The experiments carried out in this work contributed to a better understanding of the in vitro modulation of the aqueous extract of bijuí bee propolis when it comes to its biological properties applied to MN phagocytes of human blood.